Pengaruh cara pengawetan terhadap sifat fisis kulit kelinci rex berbulu - Widari, Widari (Majalah Kulit, Karet, dan Plastik, 1994)
This experiment was done to compare the preservation (curing) method of for Rex rabbit skin on their physical properties tensile strength, tear strength and stick-tear strength. The raw material used in this experiment were 36 pieces rabbit skin. The skins devided in to three curing methods were salted, dry salted and combination dry salted and poison each nine pieces respectively. Nine pieces for uncured/fresh skins used as control. The cured and uncured skins were than processed as finished leather. The physical properties of cured finish leather were analyzed and compare with physical properties of uncured leather. The physical properties of uncured leather had better quality compared than cured leather.Â INTISARIÂ Penelitian ini bertujuan untuk mengetahui pengaruh terhadap sifat fisis (kekuatan tarik, kekuatan sobek dan kekuatan jahit) kulit kelinci Rex berbulu. Materi yang digunakan adalah kulit kelinci Rex sebanyak 36 lembar, terdiri dari 9 lembar kulit awet kering menggunakan racun dan 9 lembar kulit segar sebagai kontrol. Dari pengujian fisis terhadap kulit jadinya diperoleh hasil bahwa kulit jadi yang berasal dari kulit segar kualitasnya lebih baik dibandingkan kulit yang mengalami proses pengawetan.